Gustilo-Anderson 3C femoral diaphyseal fracture with bone loss and ipsilateral Garden 3 neck fracture treated with intramedullary nailing and bone allograft - Spina, Mauro; D’Agostino, Enrico Salvatore; Zoccatelli, Fabio; Giorgio, Ilaria (Acta Biomedica Atenei Parmensis, 2025)
Segmental femoral fractures with extensive bone loss represent a rare and complex challenge in orthopedic trauma. We report a case of a 32-year-old male who sustained an open diaphyseal femoral fracture (Gustilo-Anderson type III C; AO/OTA 32C3) with concomitant femoral artery injury, a 10 cm segmental bone defect, and an ipsilateral displaced femoral neck fracture (Garden III; Pauwels III; AO/OTA 31A2). Initial management consisted of thorough surgical debridement and temporary external fixation to parzial restore femoral length, combined with vascular repair and thigh fasciotomy performed by the vascular surgery team. After five weeks of intravenous antibiotic therapy addressing postoperative infection, definitive fixation was achieved with intramedullary nailing and anti-rotational cannulated screws for the femoral neck. Nine months post-trauma, a homologous cylindrical bone graft was performed alongside lateral locked plating to support the segmental defect. At nine years follow-up, radiographs demonstrated hypertrophic callus formation and complete femoral neck consolidation without evidence of avascular necrosis. The patient exhibited full, painless hip range of motion with no limb length discrepancy and an excellent functional outcome (Harris Hip Score: 100). This case highlights the importance of a multidisciplinary approach, precise surgical timing, and patient compliance in achieving favorable outcomes in complex femoral fractures with bone loss.